The reporting of uveal melanoma cases to the cancer registry in North Carolina - Gordon, Kathleen G.; Carvajal, Richard D.; Graham, Sharnee’ L.; Houghton, Odette M. (Frontiers in Oncology, 2022)
Abstract Objective To ascertain the completeness of reporting of uveal melanoma cases in North Carolina to the state’s cancer registry. Methods This was a retrospective chart review performed at a single institution analyzing the completeness of information reported to the North Carolina Cancer Registry between 2010 and 2015. A list of all patients with uveal melanoma diagnosed, treated and/or followed at UNC-Chapel Hill between 2010-2015 was compared to the list of patients with uveal melanoma reported to the North Carolina Central Cancer registry during the same time frame. Results Based on ICD 9 and 10 codes, there were 66 patients with ciliary body or choroidal melanomas diagnosed, followed and/or treated at UNC between 2010 and 2015. Of those, 41 (62%) were on the list of cases reported through the UNC Cancer Registry to the NCCCR. A chart review of the excluded cases was performed and the following barriers to reporting of uveal melanoma were identified: lack of diagnostic imaging results, lack of histopathologic confirmation, inconsistent language used to communicate diagnosis, and lack of implementation of the North American Association of Central Cancer Registries’ National Interstate Data Exchange Agreement. Conclusions The diagnosis and treatment of uveal melanoma is unique when compared to other types of cancers. This creates significant barriers to reporting cases to state and national cancer registries. The incomplete data makes it difficult to detect changes in the incidence of uveal melanoma in North Carolina. The development of a national uveal melanoma registry should be seriously considered.